Privātās vispārizglītojošās vidusskolas stratēģija. - Griba, Margarita (Latvijas Universitāte, 2009)
Maģistra darbam izvēlēta aktuāla tēma ”Privātās vispārizglītojošas vidusskolas stratēģija”. Darba autore apskata un aprakstīja darbā skolas vēstures datus, tajā skaitā privātās izglītības iestādes kontekstā, starptautiskās izglītības sistēmas dažādas pieejas un iespējas, privātās mācību iestādes būtību, likumdošanu un finansējumu, kā arī skolotāju lomu, sabiedrības attieksmes, īpatnības un problēmas šajā procesā. Maģistra darba autore pēta vadības un mācību procesa atšķirības un kopsakarības starp valsts un privātajam vidusskolām. Pēc pētījuma rezultātiem, darba autore izstrādā privātskolas stratēģiju un secinājumus par privātizglītības nozīmi Latvijas izglītības sistēmas attīstībai.

The development of modern school in Latvia is connected with organization of private schools. The law of education allows to organize private educational institutions. The success of private school depends on experimental pedagogical activity of the headmaster. The guidance of modern schools has both to tend to achieve self-perfection, realize the part of school in market economy and to become proficient in management. Organization of private educational institutions is connected with the educational system’s reforms, possibilities of modern methods and technologies, interest of creative teachers and demands of society. Peculiarities of private schools may be investigated by answering the following questions: how parents of nowadays pupils understand the definition “private schools”, what is the difference between state and private schools pupils and what the attitude of teachers to private schools is. The author is writing this work to find the answers to these questions, to investigate peculiarities of private schools and their role in educational system, to provide effective work of private schools and to work out the conception of the development and the strategy of private school.
Strategy of a private general comprehensive school.
Keywords: Izglītības vadība